On generalized Abel summation by parts. - Yudistira Mulyadi. (2012)
This thesis focuses on the generalization of Abel Summation by Parts Formula, espe- cially in the two-dimensional case. The original Abel Summation by Parts is de ned for two 1-dimensional functions. Our main result generalizes theorems in papers on Abel Summation by Parts that have been published since late 1990s.